Modified Simulated Annealing Algorithm for optimum design of truss structures with continuous variables - Millán-Páramo, Carlos (2017)
In recent years, the importance of economic considerations in the ﬁeld of structures has motivated many researchers to propose new methods for minimizing the weight of the structures. In this work, the modified simulated annealing algorithm (MSAA), is presented to solve weight optimization of truss structures with continuous variables. To evaluate and validate the MSAA performance were studied five problems reported in the literature. The results of MSAA compared with results of other optimization algorithms show that this algorithm can generate improved designs and be effectively used in the weight minimization of truss structures.